STUDY REGARDING THE ROLE OF BARRIER MEMBRANES IN GUIDED BONE REGENERATION TECHNIQUES - Doriana Agop Forna; Alina Robu; Cristian Budacu; Marta Petre; Claudiu Topoliceanu; Stratulat Mihai Dana; Ovidiu Stamatin; Iulian Antoniac; Norina Forna (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study Resorbable barrier membranes have emerged as a crucial component of GBR procedures, facilitating the controlled healing process and promoting bone regeneration. This review aims to explore the roles, comparison and benefits of resorbable barrier membranes in guided bone regeneration. Material and methods In this scientific paper, FTIR (Fourier Transform Infrared Spectroscopy) and SEM (Scanning Electron Microscopy) analyzes were performed for four sets of collagen-based dental membranes and pericardium. The tests were conducted in the laboratories of the Faculty Materials Science and Engineering, Politehnica University Bucharest. Results The clinical applications and outcomes of resorbable barrier membranes in guided bone regeneration are extensively discussed. Studies have demonstrated the effectiveness of these membranes in enhancing bone regeneration and improving the long-term success of dental implant placements. The influence of the material from which the resorbable membranes are made on the contact angle was highlighted, even if they have the same duration of resorbability. The influence of the material from which the resorbable membranes are made on the contact angle was highlighted, even if they have the same duration of resorbability (P2, P3, P4). Conclusions Resorbable barrier membranes play a crucial role in guided bone regeneration by creating a protected environment, facilitating osteogenic cell migration, and promoting bone formation. With careful consideration of their properties and proper surgical techniques, resorbable barrier membranes offer a valuable tool in enhancing bone regeneration and achieving successful oral and maxillofacial reconstruction procedures. Further research and advancements in membrane design and clinical protocols will continue to refine and optimize their application in guided bone regeneration.